Biosynthetic process and strain improvement approaches for industrial penicillin production - Sawant, Amol M.; Vamkudoth, Koteswara Rao (Biotechnology Letters, 2022)
Penicillins and cephalosporins are the most important class of beta (beta) lactam antibiotics, accounting for 65% total antibiotic market. Penicillins are produced by Penicillium rubens (popularly known as P. chrysogenum) were used to synthesize the active pharmaceutical intermediate (API), 6-aminopenicillinic acid (6-APA) employed in semisynthetic antibiotic production. The wild strains produce a negligible amount of penicillin (Pen). High antibiotic titre-producing P. chrysogenum strains are necessitating for industrial Pen production to meet global demand at lower prices. Classical strain improvement (CSI) approaches such as random mutagenesis, medium engineering, and fermentation are the cornerstones for high-titer Pen production. Since, Sir Alexander Fleming Discovery of Pen, great efforts are expanded to develop at a commercial scale antibiotics producing strains. Breakthroughs in genetic engineering, heterologous expression and CRISPR/Cas9 genome editing tools opened a new window for Pen production at a commercial scale to assure health crisis. The current state of knowledge, limitations of CSI and genetic engineering approaches to Pen production are discussed in this review.
Keywords: beta-lactam antibiotic; Classical strain improvement (CSI); Genetic engineering; Penicillin; Penicillium chrysogenum